KDEB explains Selangor Gov't stake in SYABAS - New Sarawak, Tribune (New Sarawak Tribune, 2013)
KUALA LUMPUR: Kumpulan Darul Ehsan Berhad (KDEB),the investment arm of the Selangor government, said today the Selangor government only had a minority share limited to board representation in Syarikat Bekalan Air Selangor(SYABAS). Its President, Suhaimi Kamaralzaman, said the state government only owned 30 percent equity and had two directors in SYABAS.